Pengaruh Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan Pada Hotel Di Tarogong Kaler Garut Dengan Aksesibilitas Data Sebagai Variabel Moderasi - Salsabila Nazhipah; Irma Rosmayati; Winda Ningsih (Universitas Riau Kepulauan, 2026)
This study is motivated by the importance of financial reporting quality as a fundamental basis for managerial decision-making, particularly in the hospitality sector, which requires financial information that is timely, accurate, and reliable. The objective of this study is to examine the effect of Accounting Information Systems on the Quality of Financial Reports in hotels located in Tarogong Kaler District, Garut Regency, and to assess whether data accessibility acts as a moderating variable in this relationship. This research employs a quantitative approach using a survey method. The survey was conducted through questionnaires distributed to selected respondents using purposive sampling techniques. Furthermore, the data were analyzed using simple linear regression, and Moderated Regression Analysis (MRA). The findings indicate that both Accounting Information Systems and Data Accessibility individually have a positive and significant effect on the Quality of Financial Reports. However, data accessibility does not function as a moderating variable that strengthens or weakens the relationship between the two variables. Therefore, improvements in financial reporting quality are more directly influenced by the implementation of Accounting Information Systems and the level of data accessibility itself.